PENANGGULANGAN TINDAK PIDANA YANG TERJADI DI JALAN RAYA STUDI KASUS WILAYAH HUKUM KEPOLISIAN RESOR KOTA PEKANBARU - Pryani, Dini; R, Mukhlis; Diana, Ledy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Thuggery is all forms of crimes committed the thugs where in doing all form of action they are often in groups and from gangs. And basically the formation of cliques that became the beginning of the name of thuggery and in the end they will do various forms of crime. This act of thuggery is not set explicitly in the legislation but the action and crime thuggery is basically set in the laws and regulations of the criminal law and other legislation. Duty state police of the Republic of Indonesia is maintaining security and public order; enforcing the law; and provide protection, auspices, and service to the community. As for the propuse of writing this thesis, namely: First. To learn to cope with the crime that occurred on a Higway Police legal relic in the resort town of Pekanbaru. Second, to know the obstacles in dealing with the criminal acts thatoccur on the Highway Police jurisdiction the resort city of Pekanbaru. Third, efforts to overcome the obstacles to knowing the response criminal acts that occur on the Highway Police jurisdiction the resort city of pekanbaru.